The estimation of leap performance with maintaining open legs in grand jeté for professional ballet dancers - Kuromaru, A.; Maruyama, T. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Ballet dancers are required to perform the same beautiful movements on both sides of the body for choreographic purposes. However, the evaluation of beautiful movement is ambiguous because there is no specific index for ballet. Therefore, we interviewed ballet instructors about the grand jeté, a dynamic and frequently used movement. The respondents answered that the most beautiful moment was during the leap and it was important to keep the legs open during the leap. Therefore, maintaining the open legs and leaping is considered to be the high performance of the grand jeté. It is considered difficult to maintain more than 50% of the leg-open posture for a short period of time during leaping. But few studies have focused on ballet movement and leg-opening posture. In this study, we defined the performance of the leg-opening during the grand jeté as whether or not the legs were open for at least 50% of the leap time. The purpose of the study is to examine the relationship between the indexes and the differences in leg opening posture and movement.